ANALISIS RANTAI PASOK KELAPA DI DESA SANGKUB SATU KECAMATAN SANGKUB KABUPATEN BOLAANG MONGONDOW UTARA (Coconut Supply Chain Analysis In Sangkub Satu Village, Sangkub Sub District, North Bolaang Mongondow Regency) - Risni Tahunining; Caroline B. D. Pakasi; Charles R. Ngangi (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2021)
The objective of this research is to identify product flow, financial flow, information flow. And analyze the level of marketing efficiency in the coconut supply chain. The research was carried out from June to August 2021. The data collected were primary data obtained from farmers and traders using questionnaires, internet secondary data, and the Sangkub Satu Village Office. Sampling using purposive sampling method as many as 24 people from 52 farmers, and snowball sampling method as many as 24 farmers and 3 traders. The research result showed that (1). Coconut supply chain in the channel Farmers-Collectors-Factory based on product flow flowing from upstream to downstream where farmers process coconut into copra and sell copra to traders, traders sell copra to factories, financial flows flow from downstream to upstream where factories buy copra with a transaction via banks to traders and traders buy copra with transactions directly to farmers, the first flow of information on the direction of the factory informs copra quality and price to traders, traders informs copra prices to farmers. The second flow of information isÂ the two farmersÂ to inform the copra quality to trader and the trader will inform the factory the amount of copra to the factory. (2). The level of marketing efficiency in the coconut supply chain is seen from marketing margins, costs and profits, farmers and traders who have been efficient.